TEKNIK PENAMPUNGAN DAN FERMENTASI AIR KENCING SAPI BALI DI DESA DAUH YEH CANI, BADUNG MENJADI PUPUK ORGANIK RAMAH LINGKUNGAN - IM.S. Negara; Simpen Simpen; Arsa Arsa; Diantariani Diantariani; Miwada Miwada (Buletin Udayana Mengabdi, 2008)
ABSTRACT The activity was carried out to put to use of the urine cattle bali with fermented technology. The activity of community servece was ccaried out at Dauh Yeh Cani village, Badung regency, on Suturday, 4 August 2007. The participants from the farmers group at Dauh Yeh Cani village. The demo plots was carried out at KUBE KMM. The material of a demo plots i.e. a removal by product (urine) with feces and than its were fermented.. The products made from the activity were liquied fertilizer organic (clean governunt). The participants were curious to follow all the activities and hope for the team Unud be able to came again with a news information.